International comparison on bank capital and performance - Chu, Man Chong (2011)
This study has carried out a multivariate regression to find out the impact of capital on bank’s performance and survivability. Through the use of cross country data consisting with China, France, Japan and United Kingdom from 2003 to 2010, this study has found capital is particularly important on bank’s profitability and stock return during the financial crisis. Meanwhile, the effect of capital on large banks is relatively smaller than small to medium banks as capital is only found to be significant on them during the financial crisis. This research has also pointed out how the effect of capital on bank’s profitability varies across countries. According to the result, capital is only found to be significant for China and Japan. The different impact found on capital for different countries might due to their different banking regulations and banking structure. However, capital acts as a cushion in absorbing losses to prevent bank’s failure no matter in normal or crisis period. As a result, it is suggested banks should build up more capital during normal times in order to avoid themselves to be insolvent.